Role of Baseline Bone Scintigraphy in the Evaluation of Skeletal Metastases of Newly Diagnosed Lung Carcinoma Patients - Nahar, Kamrun; Prince, Md Sayeedul Alam; Begum, Shamim MF; Naznin, Afroza; Rahman, Farhana; Sultana, Sadia (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Lung carcinoma is the most common cancer worldwide with high potentiality of being metastasized to bone. Technetium-99m methylene diphosphonate (99mTc MDP) bone scintigraphy is a sensitive nuclear medicine imaging study to detect the skeletal metastases. The utilization of bone scan upon diagnosis of lung cancer appears to help in accurate staging of patients and planning treatment. The aim of the present study was to see the role of baseline bone scintigraphy in the newly diagnosed lung carcinoma patients and also to see the number, pattern and sites of involvement of bone as well as to evaluate the skeletal metastases according to the different histological types of lung carcinoma. Patients and Methods: This observational study was carried out at the Institute of Nuclear Medicine & Allied Sciences (INMAS), Sylhet during the period of July 2014 to June 2015. A total number of 59 lung carcinoma patients who attended at the scintigraphy division of INMAS, Sylhet within three months of their histopathological diagnosis were included in this study. Clinical staging was done from clinical evaluation (history and physical examination) and also form available investigation reports. Skeletal scintigraphy was performed by dual-head gamma camera using low-energy all purpose collimator, 2-3 hours after IV administration of 20-30 mCi of 99mTc MDP. Interpretation was done by recording the distribution of radiotracer within the skeleton along with correlation of history, physical examination, FNAC or biopsy reports and other relevant investigation findings. Results: Out of 59 patients, 43 (72.9%) were male and 16 (27.1%) were female. The age range of the patients was from 37 to 85 years with a mean (± SD) of 59.10 ± 10.43 years. The rate of lung carcinoma was highest in the age group of 55-64 years (45.7%), followed by 45-54 years (27.1%) and 65-74 years (11.9%). Incidence was lowest in patients below 45 years (6.8%) and above 75 years (8.5%). Skeletal metastases were detected in 52.54% of lung carcinoma patients where multiple lesions were seen in 87.1% of cases and solitary lesion in 12.9%. Among the metastatic lesions, 82.9% lesions were distributed in axial skeleton and 17.1% lesions were distributed in appendicular skeleton. Spine was the most frequent site of metastatic involvement in the present study which was 37.8% followed by ribs 28.0%, sternum 9.7% and pelvic bones 7.3%. Thoracic spine was found to be involved more (58.1%). Regarding patterns of metastatic lesions, 23 patients (74.1%) showed hot lesions, two patients (6.5%) showed cold lesions, four patients (12.9%) showed superscan and two patients (6.5%) showed pattern of hypertrophic osteoarthropathy. Bone metastasis was found in 75% cases of small cell lung carcinoma (SCLC) and 49.2% cases of non-small cell lung carcinoma (NSCLC). Among NSCLC, adenocarcinoma showed 62.9% metastases followed by 36.8% squamous cell carcinomas and 20.0% large cell carcinomas. In this series, clinical staging was done and 11 patients ( 18.6% ) were found in stage I, 21 patients ( 35.6% ) in stage II, 23 patients ( 39.0% ) in stage III and 04 patients ( 6.8 % ) in stage IV. Skeletal scintigraphy detected metastatic lesions in six of 11 cases (54.5 %) in clinical stage I, five of 21 cases (23.8 %) in clinical stage II, 16 of 23 cases (69.6 %) in clinical stage III and in all patients (100%) with clinical stages IV showing higher rate of bone metastases with advanced clinical stages. Conclusion: In this study, skeletal scintigraphy changed clinical staging of 27 patients. Early diagnosis of lung carcinoma, followed by bone scanning without delay helps to diagnose skeletal metastases, the presence of which is a major determinant in subsequent pathological staging and treatment planning. Bangladesh J. Nuclear Med. 19(2): 111-115, July 2016